2020
DOI: 10.1083/jcb.202003148
|View full text |Cite
|
Sign up to set email alerts
|

SLX4–XPF mediates DNA damage responses to replication stress induced by DNA–protein interactions

Abstract: The DNA damage response (DDR) has a critical role in the maintenance of genomic integrity during chromosome replication. However, responses to replication stress evoked by tight DNA–protein complexes have not been fully elucidated. Here, we used bacterial LacI protein binding to lacO arrays to make site-specific replication fork barriers on the human chromosome. These barriers induced the accumulation of single-stranded DNA (ssDNA) and various DDR proteins at the lacO site. SLX4–XPF functioned as an upstream f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 86 publications
2
10
0
Order By: Relevance
“…S2B) (42). Subsequently, excess ssDNA is generated by structurespecific endonuclease and ATR pathway is activated at the stalled then possibly collapsed fork (43). Although expression of an mCherryLacI fusion protein resulted in a robust accumulation of ATRIP, RAD9, or TOPBP1 around the arrays in EdU (5Ethynyl2′deoxyuridine)positive cells, we did not observe evident arrayspecific accumulation of PHF8 (fig.…”
Section: Phf8 Is Physically Associated With Topbp1mentioning
confidence: 71%
“…S2B) (42). Subsequently, excess ssDNA is generated by structurespecific endonuclease and ATR pathway is activated at the stalled then possibly collapsed fork (43). Although expression of an mCherryLacI fusion protein resulted in a robust accumulation of ATRIP, RAD9, or TOPBP1 around the arrays in EdU (5Ethynyl2′deoxyuridine)positive cells, we did not observe evident arrayspecific accumulation of PHF8 (fig.…”
Section: Phf8 Is Physically Associated With Topbp1mentioning
confidence: 71%
“…Chromatin immunoprecipitation was performed as described previously ( 50 ). For qPCR analysis, SYBR Premix Ex Taq II (Takara, RR081A) or TB Green Premix Ex Taq II (Takara, RR820A) was used according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…FANCP/SLX4 is a scaffolding protein that allows the engagement of multiple DNA endonucleases: MUS81, SLX1, and FANCQ/XPF/ERCC4 ( 26 , 27 ). FANCP/SLX4 is thought to be recruited by Ub-FANCD2-I, but recent reports have also shown that FANCP/SLX4 can directly recognize stalled replication forks and can be recruited to the site of damage independently from Ub-FANCD2 ( 28 , 29 ). The endonucleases coordinated by FANCP/SLX4 would cleave the phospho-backbone of the double stranded DNA, cut the DNA strand contiguous to the ICLs, and generate a DNA adduct and a DSB ( 30 ).…”
Section: Pathophysiologymentioning
confidence: 99%